2019
DOI: 10.3390/molecules24244508
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Sodium Deoxycholate Catalyzed by Gold Nanoparticles and Chiral Recognition Performances of Bile Salt Micelles

Abstract: Au nanoparticles (NPs) were prepared by UV light irradiation of a mixed solution of HAuCl4 and sodium deoxycholate (NaDC) under alkaline condition, in which NaDC served as both reducing agent and capping agent. The reaction was monitored by circular dichroism (CD) spectra, and it was found that the formed gold NPs could catalyze the oxidation of NaDC. A CD signal at ~283 nm in the UV region was observed for the oxidation product of NaDC. The intensity of the CD signal of the oxidation product was enhanced grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[28] The size of the Au NPs, prepared using sodium deoxycholate as a reducing agent, decreased with increasing sodium deoxycholate concentration. [29] Sodium glycocholate and sodium taurocholate have been utilized for the synthesis of Au NPs. [21] It was found that particles prepared using sodium taurocholate were nearly spherical in shape, whereas the use of sodium glycocholate resulted in small spherical particles and larger particles with triangular or hexagonal shape.…”
Section: Hauclmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] The size of the Au NPs, prepared using sodium deoxycholate as a reducing agent, decreased with increasing sodium deoxycholate concentration. [29] Sodium glycocholate and sodium taurocholate have been utilized for the synthesis of Au NPs. [21] It was found that particles prepared using sodium taurocholate were nearly spherical in shape, whereas the use of sodium glycocholate resulted in small spherical particles and larger particles with triangular or hexagonal shape.…”
Section: Hauclmentioning
confidence: 99%
“…[ 28 ] The size of the Au NPs, prepared using sodium deoxycholate as a reducing agent, decreased with increasing sodium deoxycholate concentration. [ 29 ]…”
Section: Synthesis and Dispersion Of Inorganic Npsmentioning
confidence: 99%
“…Similar effect was seen for Brij® O10 and SD mixture with CUR/FA. SD has been recently used as a reducing agent with oxidation happening at the hydroxyl groups to form carbonyl groups [44]. This oxidation process was UV induced hence it may contribute to further stabilisation of CUR against photodegradation.…”
Section: Assessment Of Cur Degradation Using Photospectroscopy Mass Spectrometry and Temperature Controlled 1 H Nmrmentioning
confidence: 99%
“…The oxidized product was utilized to recognize chiral enantiomers. 36 Based on the knowledge achieved in the last two decades, it had been shown that small nanocarrier systems have a prolonged blood circulation time, eluding mononuclear phagocyte systems. 20,25 Star-shaped polymers can acquire more compact shapes, architectural plasticity, and smaller hydrodynamic diameters than linear polymers.…”
Section: Introductionmentioning
confidence: 99%